BAGAIMANA KOMPTERENSI TUTOR DAN PELAKSANAAN TUTORIAL MEMPENGARUHI PRESTASI MAHASISWA: TELAAH DARI POKJAR GROBOGAN UPBJJ-UT SURAKARTA - Muhrom Ali Rozai (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2020)
The research objective was to examine the effect of pedagogic competence, professional competence, personal competence, social competence and tutorial implementation on student achievement. The design / methodology of this research was carried out on 114 non Pendas students at Pokjar Grobogan UPBJJ UT Surakarta which were explored using a questionnaire. The analysis used is multiple regression analysis. The finding of a significant positive influence between pedagogic competence, professional competence, personal competence, social competence and tutorial implementation. The limitation of this research is the difficulty of controlling the respondents, namely that the questionnaire is filled out with other students (discussion) so that the results will risk bias the results